Internationale Gerechtigkeit und institutionelle Verantwortung - Nida-Rümelin, Julian; Daniels, Detlef; Wloka, Nicole (De Gruyter, 2019)
What are the implications of globalization for moral behavior? What would global practices look like that were just for all in principle? Is it possible to generalize the basic principles of social justice as they prevail in democratic countries? Or instead, do other, possibly weaker levels of moral responsibility exist at the global level that promote global social justice based on different sets of principles?